INNOVATIVE APPROACH TECHNOLOGY TO THE INTEGRATION OF SCIENCES IN PRIMARY EDUCATION TECHNOLOGY LESSONS - Alimova Mashhuraxon Ravshanbek qizi (Galaxy International Interdisciplinary Research Journal, 2023)
The article provides information on the use of innovative approaches in technology lessons in primary education.